Buy now, pay later: balancing convenience and caution in consumer finance / Hafizah Hammad Ahmad Khan, Noorlailahusna Mohd Yusof and Fathiyah Ahmad @ Ahmad Jali - Ahmad Khan, Hafizah Hammad; Mohd Yusof, Noorlailahusna; Ahmad@Ahmad Jali, Fathiyah (Universiti Teknologi MARA, Kedah, 2024)
In an era characterized by rapid technological advancements and an increasing desire for convenience, financial services are not immune to the wave of innovation that is transforming the world. PayLater Services, a recent innovation in the financial industry, is a prime example of this. This financial solution has revolutionized the payment process for goods and services, providing greater flexibility and convenience than ever before (Cook et al., 2023).